2013
DOI: 10.1080/09593330.2013.856955
|View full text |Cite
|
Sign up to set email alerts
|

Performance of aerobic granular sludge in different bioreactors

Abstract: Inoculated sludge from the Brewery wastewater treatment plant was cultured in a sequencing batch reactor (SBR). The granular sludge was then used to process the artificial simulation wastewater to compare the performance and efficiency of the granular sludge in organic matter removal by using SBR and granular membrane bioreactor (GMBR). Results showed that the granular sludge in the SBR exhibited desirable characteristics and good removal efficiency. The mixed liquor suspended solids (MLSS) and the sludge volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 4 publications
2
6
0
Order By: Relevance
“…The development of sludge granulation is one of the important factors contributed towards the successful operation in UASB [41]. This finding is consistent with the founding by Zhao et al, [42] and Wu et al, [43], whom reported that the pollutants removal efficiency (i.e: COD) was improved by utilizing the granular sludge in wastewater treatment and the size of sludge granule could be proportional with the production of biogas.…”
Section: Biodegradability Of Rice Straw Leachatesupporting
confidence: 82%
“…The development of sludge granulation is one of the important factors contributed towards the successful operation in UASB [41]. This finding is consistent with the founding by Zhao et al, [42] and Wu et al, [43], whom reported that the pollutants removal efficiency (i.e: COD) was improved by utilizing the granular sludge in wastewater treatment and the size of sludge granule could be proportional with the production of biogas.…”
Section: Biodegradability Of Rice Straw Leachatesupporting
confidence: 82%
“…A study conducted to determine the removal of nitrogen in AGMBR reported about 60% total nitrogen removal in the AGMBR [ 111 ]. Another study to determine the performance of AGMBR reported the removal of COD, total phosphorus, nitrate-nitrogen and total nitrogen as 93.17%, 90.42%, 95% and 95%, respectively [ 157 ].…”
Section: Current Research Trends For Membrane Fouling Abatement Inmentioning
confidence: 99%
“…In recent years, there are more and more researchers focusing on the study about aerobic granular sludge (AGS), for example, it was found that the ratio of flocculent sludge should be kept a low level so as to maintain the stable operation of the granular sludge reactor because of the kinetic superiority of flocculent sludge over granular sludge, rather than microbial competition [21]. The distribution of A c c e p t e d M a n u s c r i p t extracellular polymeric substances (EPS), hydraulic shear parameters and reactor configuration have a important influence on the structural stability of AGS [22][23][24]. Moreover, the concentration of Cu2+ and carbon source also plays a key role in performance of AGS [25][26].…”
Section: Introductionmentioning
confidence: 99%